ARTE RUPESTRE AFRICANO EN LAS CUEVAS DE CUBA. LA NECESIDAD DE UN CAMBIO EN LAS HERRAMIENTAS METODOLÓGICAS - Gutiérrez Calvache, Divaldo (2012)
This paper presents a critical analysis of some philosophical elements, theoretical projections, methods and proposals used to attempt to demonstrate the possible African origin of certain Cuban rock art design, between the XVIth and XIX centuries. This analysis demonstrates that, until today, the majority of these approaches have not obtained the expected results, because they have been concentrated on morphological comparisons and mythological inductions of limited scope. In order to obtain more accurate and effective answers to this question becomes necessary a redesign of concepts and methods, as well as a change in the way rock art sites of possible African origin are approached.